Modulation of the El Niño teleconnection to the North Atlantic by the tropical North Atlantic during boreal spring and summer - Casselman, Jake W.; Jiménez Esteve, Bernat; id_orcid:0 000-0003-2706-5309; Domeisen, Daniela; id_orcid:0 000-0002-1463-929X (Copernicus, 2022)
Equatorial Pacific sea surface temperature anomalies (SSTAs) associated with El Niño–Southern Oscillation (ENSO) can influence the North Atlantic European (NAE) region. ENSO tends to be negatively correlated with the North Atlantic Oscillation in winter, while this connection is less clear in boreal spring and summer when the ENSO teleconnection encounters altered background conditions (i.e., a weaker subtropical jet), which can modulate the signal on the way to the NAE region. One such region that modulates the ENSO teleconnection to the NAE region is the tropical North Atlantic (TNA). While several mechanisms exist for this modulation, we center our analysis on the Caribbean region and the Walker cells. In order to isolate the relevant mechanism, we force an idealized atmospheric circulation model with three different seasonally varying sea surface temperature patterns that represent an ENSO event with or without the influence of the TNA, focusing on the decaying phase of ENSO in boreal spring and summer. We find that in boreal spring, the TNA modulates the ENSO teleconnection to the NAE primarily through a propagating Rossby wave train, while in summer, the TNA's influence tends to strengthen the ENSO influence over the NAE sector. Overall, this study offers a deeper understanding of the inter-basin interactions through the Walker cell following an ENSO event and the central role of tropical Atlantic SSTAs in modulating the teleconnection to the NAE region in boreal spring and summer. ISSN:2698-4016 ISSN:2698-4008